Wheat Cost-Return Budget in Southeast Kansas - O'Brien, Daniel M.; Shoup, Douglas; Ibendahl, Gregg (My University, 2015)
This publication outlines the expected costs and returns for wheat in southeast Kansas.
MF992_2015_04
Keywords: MF992; Economics; Crops; MF